Jakaba Undercover: Taxonomic Riddle and Potency in Indonesian Agriculture - Risya Ayudya Fadilah; Methodius Digna Kurnia; Ivan Permana Putra (Universitas Sebelas Maret, 2024)
Excessive use of chemical fertilizers leads to serious environmental and health issues, while organic biofertilizers offer a sustainable solution. Jakaba or “jamur keberuntungan abadi,” a local liquid organic fertilizer derived from fungi, is increasingly used by Indonesian farmers. However, its taxonomy and potential applications require further investigation. Moreover, the effects of jakaba on Fusarium and its impact on maize growth remain unexplored. This study aims to characterize jakaba comprehensively, evaluate its anti-Fusarium properties, conduct pathogenicity tests, and assess its effects on maize growth. Morphological analysis of fresh jakaba fruiting bodies was conducted, and molecular identification was performed based on the internal transcribed spacer (ITS) 1/4 regions. The antagonistic test was done using plant pathogenic fungi (Fusarium sp.). In addition, jakaba was evaluated for its impact on the vegetative growth of maize. Observations identified jakaba as belonging to the genus Corallomycetella, characterized by coral-shaped fruiting bodies with an orange hue and a white tip. The hyphae are septate, spore hyaline, and ellipsoid. The Basic Local Alignment Search Tool (BLAST) analysis revealed that jakaba was Corallomycetella repens, with a query cover of 99% and a phylogenetic tree 96% bootstrap (BS) value. Jakaba exhibits antibiosis activity against Fusarium sp., with an inhibition rate of 5.64%. Although C. repens has been previously identified as a cause of root rot in Indonesia, the current study reveals that jakaba is not pathogenic to maize. Furthermore, the application of jakaba’s liquid organic fertilizer at a concentration of 40 ml l-1 significantly increased plant height, leaf length, leaf width, and stem diameter compared to other treatments. These findings highlight jakaba potential as a biofertilizer.